Democratic citizenship education: Towards a model for establishing democratic mathematics teacher education - Olawale, B. E.; Mncube, V.; Harber, C. R. (South African Journal of Higher Education, 2021)
This article provides an explication of the concepts of democracy and democratic citizenship from a political dimension, it also offers insight into the nature of democracy and democratic citizenship in post-apartheid South Africa. The article further outlines the relationship between mathematics and democracy, as well as a number of pedagogical approaches which are capable of fostering democratic principles in mathematics education classrooms. Finally, the article proposes a model which encompasses a trilogy of democratic principles; humanising pedagogy; and social, cultural, economic and political issues which can be employed in preparing mathematics student teachers to become fully democratic citizens.